PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP PERMASALAHAN AGENSI PADA PENENTUAN STRUKTUR PEMBIAYAAN DAN KEPEMILIKAN MANAGERIAL PERUSAHAAN - Sasono Adi (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2014)
This study aims to investigate wether there is a significant effect on the role of independent commissioner and audit committees in relation to agency problems of corporate financial structure. Simultaneous linear regression is used. Empirical tests conducted on listed manufacturing companies by using purposive sampling. The results show that there is a negative relationship between the existance of an independent commissioner with the level of leverage. These findings demonstrate that the role of independent commissioners in an effort to reduce the risk of default. But no significant evidence is obtained that the existence of an independent commissionermay reduce agency problems in the prensence of managerial ownership. It also shows that the existence of an audit committee may reduce the managers’ incentives to perform opportunistic actions in determining the financing structure. The result of this study also indicate that leverage can be an alternative to monitor the managerial ownership.